2018
DOI: 10.1088/1367-2630/aaf25d
|View full text |Cite|
|
Sign up to set email alerts
|

Heterogeneous behavioral adoption in multiplex networks

Abstract: Heterogeneity is found widely in populations, e.g. different individuals have diverse personalities and a different willingness to accept novel ideas or behaviors. Whereas population heterogeneity is rarely considered in studying the social contagions on complex networks, especially on multiplex networks. To explore the effect of population heterogeneity on the dynamics of social contagions, a novel model based on double-layer multiplex networks is proposed, in which information diffuses synchronously on the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Therefore, it is important to conduct extensive research on the influence of media and interpersonal relationships on public opinion.In recent times, various models and simulation technologies have become available for the study of public opinion propagation. [3][4][5][6][7][8] Traditionally, the study of public opinion propagation was based on infectious disease models, such as SIS, SIR and SEIR models. [9][10][11] Wang explored the mechanisms of information propagation, including stifling, latent and forgetting mechanisms, to develop a refined SEIR model.…”
mentioning
confidence: 99%
“…Therefore, it is important to conduct extensive research on the influence of media and interpersonal relationships on public opinion.In recent times, various models and simulation technologies have become available for the study of public opinion propagation. [3][4][5][6][7][8] Traditionally, the study of public opinion propagation was based on infectious disease models, such as SIS, SIR and SEIR models. [9][10][11] Wang explored the mechanisms of information propagation, including stifling, latent and forgetting mechanisms, to develop a refined SEIR model.…”
mentioning
confidence: 99%
“…In the linear threshold model [16,17], the dynamics of social contagions was regarded as a Markov process. In recent years, researchers found that the social reinforcement effect is based on the memory characteristic, and many distinct non-Markovian models [18][19][20][21][22][23][24][25][26][27][28] have been proposed. Wang et al [18] proposed an edge-based compartmental (EBC) theory to qualitatively analyze the steady state of the dynamics of social contagions with nonredundant information memory characteristic and found that the change of some structural parameters (e.g., the heterogeneity of the network structure) or dynamic factors (e.g., the adoption threshold) will cause the crossover phenomenon of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, various types of social networks such as Facebook [9], Twitter [10], Weibo [11], and Wechat [12] have been used. Social networks are important in information transmission between users [13], such as commodity recommendation [14], news spreading [15,16], advertisement di usion [17,18], health behavior adoption [19], discovery of new friends [20], and social innovation propagation [21]. In addition, understanding the mechanism of information spreading in social networks can facilitate in the design of antivirus strategies [22][23][24], control rumors [25], avoid economic risks [26,27], restrain social unrest [28], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Wide-ranging factors have been investigated, such as the initial seed size [36], clustering coe cient [37], community structure [38], temporal network [39], role of synergy [40,41], heterogeneous adoption thresholds [42], and limited imitation [43][44][45]. Additionally, information spreading on a multiplex network [46][47][48] has aroused the interest of researchers who perform numerous investigations about communication channel alternations on multiplex networks [49], heterogeneous behavioral adoption on multiplex networks [16], opinion competition on multiplex networks [50], e ect of multiple social networks on user awareness [51], social support for suppressing epidemics on multiplex networks [52], the interplay of social influence in multiplex networks [53], replicator dynamics on multiplex networks [54], etc.…”
Section: Introductionmentioning
confidence: 99%